Basel III capital requirements and heterogeneous banks - Carola Müller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
I develop a theoretical model to examine the effect of capital requirements on risk taking and market structure of banks. Within a portfolio choice model, I allow for heterogeneous productivity among banks and consider the simultaneous capital regulation with a leverage ratio and a risk-weighted ratio. Regulators face a trade-off between the efficient allocation of resources and financial stability. In an oligopolistic market, risk-weighted requirements incentivise banks with high productivity to lend to low-risk firms. When a leverage ratio is introduced, these banks lose market shares to less productive competitors and react with risk-shifting into high-risk loans. While average productivity in the low-risk market falls, market shares in the high-risk market are dispersed across new entrants with high as well as low productivity.
Additional information: A completely revised version of this paper has been published as Müller, Carola: Capital Requirements, Market Structure, and Heterogeneous Banks. IWH Discussion Papers 15/2022. Halle (Saale) 2022. http://hdl.handle.net/10419/256924; More recent version: http://hdl.handle.net/10419/256924
Keywords: G11; G21; G28; 330; banking regulation; heterogeneous banks; banking competition; capital requirements; leverage ratio; Basel III